Answers

2015-04-21T10:52:04+05:30
As gravitational force is given by Gm1×m2
                                                  r²
F=Gm1×m2/r²⇒G=Fr²/m1×m2
G=[MLT-²] [L²]/[M2]    as force dimensional formula is M1L1T-2
G=[M-1L³T-2]
1 5 1
2015-04-21T11:10:35+05:30
Multiply both the side of the equation by r∧2 
Fr∧2= G m1  m2 
divided by side m1  m2
of force is measured in newtons ; r in meters ; m1 m2  in kg 
[units of G] = Nm∧2/kg∧2
Newton isn't a base unit, so let's pull out  the equation from Newtons' Second Law:
FORCE=MASS * ACCELERATION 
N= Kg * m/s∧2
substituting that equation for N 
[units of G] =(kg.m/s∧2)(m∧2/kg∧2)
[units of G] = m∧3/(kg.s∧2) 
[units of G]=m∧3.kg∧-1s∧-2
in term of [M],[L] AND[T]
DIMENSTIONS OF GRAVITATION CONSTANT=G=[L]∧3.[M]∧-1.[T]∧-2 


1 5 1